Between limits and possibilities of school geography - Oliveira Cruz, Dayana Aparecida Marques (Revista Ensino de Geografia (Recife), 2020)
Faced with the transformations of contemporary geographical space, reflecting on the world is an increasingly complex and necessary task. Geography has a fundamental role, as it enables such discussions in the school environment, through geographical knowledge, thus contributing to the citizen's formation. The aim of this text is to reflect on the potential of school geography for citizen formation, as well as to indicate the limits that must be overcome. This article is the result of reflections from a literature review on the subject, whose objective is to reflect on the potential of school geography for citizen formation. The ideas discussed here refer to a bibliography of critical theoretical-methodological matrix that seeks to analyze the contradictions and possibilities of geography in the context of Brazilian education.